DICŢIONARUL LIMBII ROMÂNEŞTI DE AUGUST SCRIBAN: (Etimologii, înţelesuri, exemple, citaţiuni, arhaisme, neologisme, provincialisme) - MOŢOC, Radu (BIBLIOPOLIS, 2020)
The author presents the history of elaboration of the most important dictionary of the Romanian language, from the category of lexicographical works, elaborated by a single person. This is the Dictionary of the Romanian language by August Scriban, who combined efficiently the lexicographical experience from Romania of 19th century. The paper presents the biography of the scientist A. Scriban, representative of an important dinasty of Romanian intellectuals. Also, are described the specificities of this scientific work, the elements that make the Dictionary of A. Scriban a particularly valuable reference source to date.